Analisis persistensi inflasi di Provinsi Jambi - Sophia, Aya; Safri, Muhammad; Achmad, Erni (Jurnal Paradigma Ekonomika, 2022)
This study aims to analyze the inflation persistence level in Jambi Province and the factors that influence it. By using the univariate autoregressive (AR) model, the persistence level is measured in general, disaggregation, commodity groups, and selected commodities. Multiple regression models are used for the factors that influence inflation. The observation period is January 2019 to December 2021. The results show that the persistence of general inflation in Jambi Province was low. However, high persistence was in core inflation and administered prices, 9 commodity groups, and several commodities contributing to inflation and deflation. High persistence in several commodities caused by supply side factors (changes in global commodity prices, rising prices of imported raw materials, and tariff adjustment policies by the Government). Inflation persistence is also influenced by expectations dominated by backward looking, as well as the demand side (the COVID-19 pandemic, credit growth, and the BI7DRR interest rate).